Factors that influence the financial independence among employee: a study at Koperasi Permodalan Felda Malaysia Berhad (KPF) / Nur Amanina Abd Rahim - Abd Rahim, Nur Amanina (2015)
This research is conducted in purpose to determine the most influence factors that affect the financial independence. There are three variables that have been determined as the influenced factors based on the studies that have been done before. The three independent variables are financial literacy, financial self-efficacy and financial socialization whereby the dependents variables is financial independence. The researcher targeted 100 respondents at Koperasi Permodalan Felda Malaysia Berhad. Approximately of 100 questionnaires have been distributed and collected back by hand and the result and data have been recorded. The result and data of the findings have been analyzed by using the SPSS software. From the result, it can be conclude that there are significant relationships between the independents variables with the dependent variables. Besides that, the independent variables also give influence to the dependent variables. As for the conclusions, the researcher has suggested some recommendations for this study.